Expanding the phenotypic and allelic spectrum of SMG8: Clinical observations reveal overlap with SMG9‐associated disease trait. Issue 2 (10th November 2021) - Abdel‐Salam, Ghada M. H.; Duan, Ruizhi; Abdel‐Hamid, Mohamed S.; Sayed, Inas S. M.; Jhangiani, Shalini N.; Khan, Ziad; Du, Haowei; Gibbs, Richard A.; Posey, Jennifer E.; Marafi, Dana; Lupski, James R.
Abstract: SMG8 (MIM *617315) is a regulatory subunit involved in nonsense‐mediated mRNA decay (NMD), a cellular protective pathway that regulates mRNA transcription, transcript stability, and degrades transcripts containing premature stop codons. SMG8 binds SMG9 and SMG1 to form the SMG1C complex and inhibit the kinase activity of SMG1. Biallelic deleterious variants in SMG9 are known to cause a heart and brain malformation syndrome (HBMS; MIM #616920), whereas biallelic deleterious variants in SMG8 were recently described to cause a novel neurodevelopmental disorder (NDD) with dysmorphic facies and cataracts, now defined as Alzahrani–Kuwahara syndrome (ALKUS: MIM #619268). Only eight subjects from four families with ALKUS have been described to date. Through research reanalysis of a nondiagnostic clinical exome, we identified a subject from a fifth unrelated family with a homozygous deleterious variant in SMG8 and features consistent with ALKUS. Interestingly, the subject also had unilateral microphthalmia, a clinical feature that has been described in SMG9 ‐related disorder. Our study expands the phenotypic spectrum of SMG8 ‐related disorder, demonstrates an overlapping phenotype between SMG8 ‐ and SMG9 ‐related rare disease traits, provides further evidence for the SMG8 and SMG9 protein interactions, and highlights the importance of revisiting nondiagnostic exome data to identify and affirm emerging novel genes for rare disease traits.